Javanese Ginseng Root Extract (Talinum Paniculatum (Jacq) Gaertn) to Increase Superoxide Dismutase Activities in White Male Sprague Dawley Rats by Using a Forced Swimming Test Model - Adies Riyana; Fathurrahman Fathurrahman; Erfan Roebiakto (Tropical Health and Medical Research, 2023)
Continuously performing heavy activities will damage tissues and cells and cause oxidative stress. Fortunately, this damage can be reduced by giving antioxidants to reduce free radicals. This study uses the forced swimming test model to determine the effect of Javanese ginseng root extract on superoxide dismutase levels in male white Sprague Dawley rats. The samples were 30 white Sprague Dawley rats divided into five groups: the negative control group, the positive control group, treatment group 1 receiving Javanese ginseng extract at a dose of 0.35mg/200g BW/day, treatment group 2 receiving a dose of 0.70mg/200g BW/day, and treatment group 3 receiving a dose of 1.4mg/200g BW/day. On days 28 and 35, the rats were treated with the FST model. Meanwhile, on days 28 and 35, SOD levels were measured using the xanthine-xanthine oxidase method. The effect was analyzed using statistical analysis. The administration of Javanese ginseng extract at doses of 0.35 mg/200g BW rats/day, 0.70mg/200g BW rats/day, and 1.40 mg/200g BW rats/day could significantly increase SOD levels (p < 0.05). The administration of 1.40 mg/200g BW rats/day could increase a SOD level up to normal and give the same effect as the administration of xanthine (p > 0.05) does. In conclusion, the administration of Javanese ginseng extract significantly increases SOD levels in the rats by using the FST model. This study suggests to increases the potential of Javanese ginseng root as a natural-based antioxidant supplement by investigating human subjects, especially athletes and bodybuilders